2012
DOI: 10.2147/jir.s29044
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of niacin-induced prostaglandin D2 generation by omega-3 fatty acids in THP-1 macrophages and Langerhans dendritic cells

Abstract: Niacin, also known as nicotinic acid, is an organic compound that has several cardio-beneficial effects. However, its use is limited due to the induction of a variable flushing response in most individuals. Flushing occurs from a niacin receptor mediated generation of prostaglandins from arachidonic acid metabolism. This study examined the ability of docosahexaenoic acid, eicosapentaenoic acid, and omega-3 polyunsaturated fatty acids (PUFAs), to attenuate niacin-induced prostaglandins in THP-1 macrophages. Nia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…However, this method only allowed to suppress one of the pathways causing the side effect, which made it impossible to eliminate it completely. Some researchers were concerned that suppression of PGD2 could potentially impact the antiinflammatory action of nicotinic acid, such as PGD2induced inhibition of antigen-presenting Dendritic Cells (DC) activation in inflammation (VanHorn et al, 2012). A study involving mouse models has demonstrated that shortterm administration of niacin can suppress the retention of DC in lymph nodes and that this effect is not abolished by naproxen-induced suppression of prostaglandin generation (Krmeska et al, 2022).…”
Section: Non-lipoprotein-related Effects Of Niacinmentioning
confidence: 99%
“…However, this method only allowed to suppress one of the pathways causing the side effect, which made it impossible to eliminate it completely. Some researchers were concerned that suppression of PGD2 could potentially impact the antiinflammatory action of nicotinic acid, such as PGD2induced inhibition of antigen-presenting Dendritic Cells (DC) activation in inflammation (VanHorn et al, 2012). A study involving mouse models has demonstrated that shortterm administration of niacin can suppress the retention of DC in lymph nodes and that this effect is not abolished by naproxen-induced suppression of prostaglandin generation (Krmeska et al, 2022).…”
Section: Non-lipoprotein-related Effects Of Niacinmentioning
confidence: 99%
“…However, the predominant side effect of NA includes flushing which occurs mostly due to immediate-release nicotinic acid (IRNA) and the initial doses of extended-release nicotinic acid (ERNA) [5] . Flushing occurs when the body releases prostaglandin D2 and prostaglandin E2 from cells called Langerhans cells, which is found in the skin, as well as macrophages [7] .…”
Section: Introductionmentioning
confidence: 99%